2020
DOI: 10.1080/13607863.2020.1720599
|View full text |Cite
|
Sign up to set email alerts
|

Group singing improves quality of life for people with Parkinson’s: an international study

Abstract: Objectives: Group singing has been reported to enhance quality of life (QoL) and mental health in older people. This paper explored whether there are differences in the effects of group singing intervention on people with Parkinson's (PwPs) in Australia, UK and South Korea. Methods: The study included PwPs (N ¼ 95; mean age ¼ 70.26; male 45%) who participated in a standardised 6-month weekly group singing programme. Parkinson's health-related QoL measure (PDQ39) and mental health assessment (DASS) were adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
1
17
0
1
Order By: Relevance
“…Compared to usual care, Pantelyat et al [47] found a beneficial effect of the drum circle, while Pohl et al [44] found the same for RGRM M, as did Spina et al [45] Compared to physiotherapy, Pacchetti et al [46] found a beneficial effect of instrumental musical improvisation on health-related quality of life. Four studies assessed the impact of a singing intervention on quality of life [48][49][50][82][83][84][85]. Of these, Matthews et al [50] used a RCT design compared to a passive music appreciation activity, while Tamplin et al [48,49] used a non-randomised controlled trial design with various comparators, the limitations of which were discussed above.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Compared to usual care, Pantelyat et al [47] found a beneficial effect of the drum circle, while Pohl et al [44] found the same for RGRM M, as did Spina et al [45] Compared to physiotherapy, Pacchetti et al [46] found a beneficial effect of instrumental musical improvisation on health-related quality of life. Four studies assessed the impact of a singing intervention on quality of life [48][49][50][82][83][84][85]. Of these, Matthews et al [50] used a RCT design compared to a passive music appreciation activity, while Tamplin et al [48,49] used a non-randomised controlled trial design with various comparators, the limitations of which were discussed above.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Four studies assessed the impact of a singing intervention on quality of life. [49][50][51][83][84][85][86]. Of these, Matthews et al [51] used a RCT design compared to a passive music appreciation activity, while Tamplin et al [49][50] used a nonrandomised controlled trial design with various comparators, the limitations of which were discussed above.…”
Section: Quality Of Lifementioning
confidence: 99%
“…General quality of life was assessed by three studies. Both Irons et al [83][84] and Matthews et al [51] used the Parkinson's Disease Questionnaire 39 Items (PDQ-39), [87], while Stegemöller et al [85][86] used the World Health Organization Quality of Life questionnaire (WHO-QOL). [88] Voice-related quality of life (VRQoL) [89] was assessed by two studies.…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Four studies assessed the impact of a singing intervention on quality of life. [49][50][51][83][84][85][86]. Of these, Matthews et al [51] used a RCT design compared to a passive music appreciation activity, while Tamplin et al [49][50] used a non-randomised controlled trial design with various comparators, the limitations of which were discussed above.…”
Section: Quality Of Lifementioning
confidence: 99%